Application and growth of long-range communications technology in vehicular communications - Siti Fatimah Abdul Razak; Sumendra Yogarayan; Noor Hisham Kamis; Mohd Fikri Azli Abdullah; Ibrahim Yusof (Institute of Advanced Engineering and Science, 2023)
Long range communications technology (LoRa) has been widely used in a variety of applications and researched in different domains to exploit its full potential. Its openness makes it ideal for a variety of internet of things (IoT) installations which further allows opportunities for viable solutions in vehicular communications. Hence, a bibliometric analysis was performed to distinguish the application and growth of the technology specifically in vehicular communications. The scoping review processes from Arksey and O’Malley was applied to guide the review process. The selected scholarly works adhered to the PRISMA-Sc framework where 385 articles from two main electronic databases, i.e., Scopus and Science Direct which discussed LoRa in vehicular communications contexts were assessed. This study aims to: i) examine how LoRa’s research has grown from year 2010 to 2021 among the scholars; ii) determine key areas discussed in LoRa’s vehicular communications research. Findings from 70 studies in the final analysis indicated that LoRa has been widely studied based on application, theoretical or protocol and performance. However, it has not been widely explored in vehicular context. Hence, our findings support the global research community in this context.